Cross - cultural Business, Peruvian Business: Origins, beliefs, customs, traditions and fusions - Linares Vizcarra, Mitzi Lourdes Del Carmen (2022)
In this document, we will determine the importance of knowing multiculturalism from the millenary origin of Peru and the way in which business takes shape, considering the customs, beliefs, traditions and mergers that continue in force over time, which influence in a way preponderant in the process of intracultural negotiation. Peru, from its beginnings, is constituted by all the bloods, so it is facilitated to make bonds of trust, to evaluate a business possibility, putting the value of its ancestral culture, the affability that characterizes the Peruvian, the fusion of its Meals, tourist places. Through the times, Peru has had to overcome several social, internal, and other conflicts that were originated by migrants, which caused great social conflicts and economic instability, resulting in a culture of informality in business, raising capital in a sui way generis, in the form of collection, cooperation activities between families and neighborhoods, called polladas, managing to gather small and medium capitals, appearing an infinity of single-person and family enterprises. Interculturality for business, from Peru is revealed through business innovation and benchmarking in order to achieve the conquest of new markets in America, Asia and Europe, mainly. Finally, the bibliographic references used to support the information are indicated.